Unruptured Intracranial Aneurysms- Pathogenesis and Individualized Management - Etminan, Nima; Dörfler, Arnd; Steinmetz, Helmuth (Deutsches Ärzteblatt international, 2020)
BACKGROUND: About 2 million adults in Germany harbor an unruptured intracranial aneurysm (IA). Rupture can lead to a life-threatening subarachnoid hemorrhage. If an IA is detected incidentally in cranial imaging, it must be decided how to proceed. METHODS: This review includes key publications that were identified by a selective search in the PubMed database using the search term "unruptured intracranial aneurysms," which was performed in July 2019, and based on information obtained from the German Federal Statistical Office on the frequency of the hospital discharge diagnosis "cerebral aneurysm," excluding the diagnosis "subarachnoid hemorrhage," in Germany from 2005 to 2017. RESULTS: The number of patients in Germany who were admitted or treated for an unruptured IA increased by a factor of 2.3 from 2005 to 2017. The average 5-year rupture risk of approximately 3% must be weighed against the approximately 4% risk associated with an endovascular or microneurosurgical treatment. This emphasizes the need for more precise data on the risk of rupture and for algorithms enabling individualized decision-making for patients with unruptured IA. Risk factors such as IA morphology, arterial hypertension, active smoking, and alcohol consumption (>150 g/week) can markedly increase the risk of rupture, which is generally relatively low. Growing aneurysms are 12 times more likely to rupture than stable ones. Follow-up imaging is thus essential whenever observation rather than intervention is chosen as the initial management. CONCLUSION: Patients with unruptured IA should be massessed and managed individually. It is also important that risk factors should be treated, if present. Eligible patients are currently being recruited for a phase III clinical trial on the efficacy of blood pressure reduction combined with acetylsalicylic acid intake to counteract inflammatory processes in the arterial wall.
CRIS-Team Scopus Importer:2020-06-05